IFN signaling and neutrophil degranulation transcriptional signatures are induced during SARS-CoV-2 infection - Bruce A. Rosa (Nature Portfolio, 2021)
Rosa et al. find that genes associated with Interferon (IFN) signaling, neutrophil degranulation and innate immune pathways are induced in the lungs of macaques in response to SARS-CoV-2 infection, whereas genes associated with collagen formation and regulation are reduced. Authors also note an overlap of genes associated with SARS-CoV-2 infection and tuberculosis, altogether providing new insights into the immunopathogenesis of COVID-19 disease.